Implementasi Pasal 54 Undang-Undang No 35 Tahun 2014 Pada Anak Yang Menjadi Korban Bullying di Kota Surakarta - Wida Nur Hanita; Aris Prio Agus Santoso; Kresna Agung Yudhianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Article 54 of Law No. 35/2014 on Child Protection, an amendment to Law No. 23/2002, states that children in the educational environment must be protected from physical and psychological violence, sexual crimes, and other crimes that may be committed by educators, education personnel, fellow students, or other parties. However, despite this regulation, cases of bullying in schools still occur frequently. This study aims to evaluate the application of Article 54 of Law No. 35 of 2014 concerning Child Protection and legal protection efforts for children who are victims of bullying with a legal certainty approach. The research method used is descriptive with qualitative data analysis. The results showed that Article 54 has been well implemented by the Surakarta City Office of Women's Empowerment and Child Protection and Population Control and Family Planning. They conduct socialization in schools and communities as a preventive measure and assist the mediation process for case resolution as a repressive measure. In addition, for the legal protection of child victims of bullying with a legal certainty approach, the Office also integrates bullying prevention and handling programs, facilitates and fosters education units, and provides educational facilities.